Investigations into the Flexural-Torsional Buckling Behavior of Steel Open-Section Beam-Columns - Anna M. Barszcz; Marian A. Gizejowski; John P. Papangelis (Buildings, 2023)
This paper is in the field of elastic flexural-torsional buckling of steel beam-columns of bisymmetric narrow-flange and wide-flange I-section shape. Investigations are focused on the derivation of the strain components and the energy equation, based on the displacement-field formulation in the deflected configuration. At the same time, a review of analytical solutions based on the classical and refined energy-equations are summarized, presented and discussed. The relationship between the maximum in-plane bending moment and the compressive force of beam-columns is the main objective of this research investigation. Simple boundary conditions of end-sections free to deflect and to warp are considered, together with an arbitrary loading-pattern. The principle of superposition and the moment amplification rule for considering the second-order effects are widely used. The main conclusions are drawn in relation to the flexural-torsional resistance-evaluation design of steel beam-columns in modern design codes for steelwork.